2015
DOI: 10.1038/srep14113
|View full text |Cite
|
Sign up to set email alerts
|

Bell’s measure and implementing quantum Fourier transform with orbital angular momentum of classical light

Abstract: We perform Bell’s measurement for the non-separable correlation between polarization and orbital angular momentum from the same classical vortex beam. The violation of Bell’s inequality for such a non-separable classical correlation has been demonstrated experimentally. Based on the classical vortex beam and non-quantum entanglement between the polarization and the orbital angular momentum, the Hadamard gates and conditional phase gates have been designed. Furthermore, a quantum Fourier transform has been impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 41 publications
(59 reference statements)
0
27
0
Order By: Relevance
“…For instance, the Laguerre-Gaussian modes of classical optical beams we exploit here are OAM eigenstates and solutions of the paraxial wave equation in cylindrical coordinates [31,32]. Thus, OAM and polarization can be chosen as two proper DOFs to encode the four basis states of one ququart, and we particularly describe them by a slightly modified version of the bra-ket notation of quantum states for clarity as [33]…”
Section: Quantum Permutation Algorithmmentioning
confidence: 99%
“…For instance, the Laguerre-Gaussian modes of classical optical beams we exploit here are OAM eigenstates and solutions of the paraxial wave equation in cylindrical coordinates [31,32]. Thus, OAM and polarization can be chosen as two proper DOFs to encode the four basis states of one ququart, and we particularly describe them by a slightly modified version of the bra-ket notation of quantum states for clarity as [33]…”
Section: Quantum Permutation Algorithmmentioning
confidence: 99%
“…The R. Schützhold’s QPR algorithm is analytically described in the Methods section splitting it into five steps. The most complex parts are the quantum black box 14 , or BB , and the quantum Fourier transform (QFT) 14,15 . The classical computing subunit is needed to run calculations of Laue’s equations in order to localize and specify candidate line-patterns.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that the quantum bound exists similarly in classical microwaves. The local and nonlocal correlations in the classical optical beams, which violate the Bell inequality, have been demonstrated in a series of works3435363738394041. However, the KCBS contextuality has not been studied in classical wave systems so far.…”
mentioning
confidence: 99%